Fibrosis-4 index as a predictor for mortality in hospitalised patients with COVID-19: a retrospective multicentre cohort study. Issue 11 (12th November 2020) - Park, Jung Gil; Kang, Min Kyu; Lee, Yu Rim; Song, Jeong Eun; Kim, Na Young; Kweon, Young Oh; Tak, Won Young; Jang, Se Young; Lee, Changhyeong; Kim, Byung Seok; Hwang, Jae Seok; Jang, Byoung Kuk; et al.
Abstract : Objective: The reliable risk factors for mortality of COVID-19 has not evaluated in well-characterised cohort. This study aimed to identify risk factors for in-hospital mortality within 56 days in patients with severe infection of COVID-19. Design: Retrospective multicentre cohort study. Setting: Five tertiary hospitals of Daegu, South Korea. Participants: 1005 participants over 19 years old confirmed COVID-19 using real-time PCR from nasopharyngeal and oropharyngeal swabs. Methods: The clinical and laboratory features of patients with COVID-19 receiving respiratory support were analysed to ascertain the risk factors for mortality using the Cox proportional hazards regression model. The relationship between overall survival and risk factors was analysed using the Kaplan-Meier method. Outcome: In-hospital mortality for any reason within 56 days. Results: Of the 1005 patients, 289 (28.8%) received respiratory support, and of these, 70 patients (24.2%) died. In multivariate analysis, high fibrosis-4 index (FIB-4; HR 2.784), low lymphocyte count (HR 0.480), diabetes (HR 1.917) and systemic inflammatory response syndrome (HR 1.714) were found to be independent risk factors for mortality in patients with COVID-19 receiving respiratory support (all p<0.05). Regardless of respiratory support, survival in the high FIB-4 group was significantly lower than in the low FIB-4 group (28.8 days vs 44.0 days, respectively, p<0.001). A number of risk factors were also significantly related to survival in patients with COVID-19 regardless of respiratory support (0–4 risk factors, 50.2 days; 49.7 days; 44.4 days; 32.0 days; 25.0 days, respectively, p<0.001). Conclusion: FIB-4 index is a useful predictive marker for mortality in patients with COVID-19 regardless of its severity.